Film representations of the Rwandan Genocide - Rwafa, Urther (Taylor & Francis (Routledge), 2016)
In 1994 Rwanda experienced a devastating genocide in which nearly a million Tutsi and moderate Hutu were killed by Hutu extremists. Written scholarly works explain the Rwandan genocide in historical terms. Academic work on media and the genocide tend to emphasise the role played by Radio-Television Libre Des Mille Collines (RTLM) and the newspaper Kangura in instigating the Rwandan genocide. A steady output of literature on the depiction of the genocide in film is emerging but it is fragmentary, and appears in journals that are not easily accessible. The little material research on the Rwandan genocide film does not pay sufficient attention to the stereotyped language of film and how these manifest themselves through verbal, visual, sound, colour and silence aspects which constitute the semiotic system of film. This article, therefore, explores how the Rwandan genocide is represented through the documentary films A good man in hell (2002) and Keepers of memory (2004), and the feature films Hotel Rwanda (2004) and Sometimes in April (2005). These films have been sampled first because they all focus on the Rwandan genocide; second because the films purport to approach the subject of the genocide from different perspectives. Film is an important medium for socialisation.